Dollhouse And Mrs. Potato Head : Figurative Language Used In Melanie Martinez Selected Songs - Khilda Umi Rahmah; Wiutami Danesha Afrianto; Aidil Syah Putra (Indonesian Journal Publisher, 2024)
This study explores the use of figurative language in Melanie Martinez's songs